Improving SMEs Production Performance through Local Brand and Augmented Reality: Evidence from Sumatera of Indonesia - Roymon Panjaitan (Universitas Negeri Malang, 2022)
This research aims to discuss the performance relationships of small-medium enterprise production mediated by local brand empowerment as well as investigates the role of technology adaptation of livelihood activities, fast-moving enterprise, and government policy support. This study involved 115 micro small business activists and medium respondents in the Sumatran region. A compound path test of SEM-PLS is used in this study to obtain data from the analysis of the path mediated by local brand empowerment, augmented reality preference, and acceptance of adaptive technology moderation for production performance enhancement. The findings indicate that fast-moving enterprise and government policy have a positive impact, while livelihood activities negatively impact local brand empowerment, and local brand empowerment negatively correlates to production performance. The direct stimulus of livelihood activities is meaningless, but government policy support is meaningful to the increased production of SMEs. The contribution of this study is found in the conceptual model of the acceptance of technological adaptation and optimization capabilities of the use of augmented local brand applications empowerment to increase the production of small and medium enterprises. Keywords: Augmented Reality, Local Brand empowerment, Government Support, Product Performance